Nonvolatile bipolar resistive switching in Ba-doped BiFeO3 thin films. (July 2015) - Deng, Haoliang; Zhang, Ming; Wei, Jizhou; Chu, Shangjie; Du, Minyong; Yan, Hui
Highlights: Bi0.8 Ba0.2 FeO3 (BBFO) was grown on Nb:SrTiO3 (NSTO) (1 0 0) by PLD. Nonvolatile bipolar resistive switching behavior in an Au/BBFO/NSTO structure. The resistive switching was attributed to the migration of oxygen vacancies. Abstract: The Bi0.8 Ba0.2 FeO3 (BBFO) thin film was deposited on the conducting Nb:SrTiO3 (NSTO) (1 0 0) single crystal substrate by pulsed laser deposition. Nonvolatile bipolar resistive switching effect was observed in an Au/BBFO/NSTO capacitor structure. By changing the polarity of the external pulsed voltage, the device could be switched reversibly between two stable resistance states. The resistive ratio is about 10 at a read voltage of −0.5 V after applying ±1.5 V pulse voltages. The mechanism of the resistive switching behavior could be attributed to the electric field induced migration of oxygen vacancies, which changes the height and width of the barrier at the BBFO/NSTO interface.